Microbiological spectrum of organisms in patients undergoing external ventricular drain insertion at a tertiary care hospital - Afreen, Mahrukh; Syed Vaqar Hussain; Aleezay Irfan; Talha Rasool; Muhammad Nadeem; Sumbal Nawaz (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the incidence, causative pathogens, and impact of external ventricular drain-related infection on disease prognosis. Method: The observational, cross-sectional study was conducted September 2022 to March 2023 after obtaining approval from the ethics review board of Shifa International Hospital, Islamabad, Pakistan, and comprised patients having no prior cerebrospinal fluid infection. The patients underwent external ventricular drain administration as part of their treatment. Unneeded antibiotics or cerebrospinal fluid sampling before removing the drain were avoided. External ventricular drain-related infection was defined as pathogenic growth on one or more cerebrospinal fluid culture/sensitivity test post-insertion of the drain. Data was analysed using SPSS 26. Results: Of the 74 patients, 42(56.8%) were males and 32(43.2%) were females. Overall, 25(33.8%) patients were aged 20-50 years. A total of 86 external ventricular drain were inserted for a mean period of 10.77+/-7.42 days (range: 1-40), with a total of 797 catheter days. Hydrocephalus 21(28.4%) and tumours 20(27%) were the most common aetiologies for external ventricular drain, but no significant aetiological risk factors for external ventricular drain-related infection were identified (p>0.05). Overall, 39(52.7%) patients recovered with external ventricular drain removal, and 12(16.2%) needed a shunt. External ventricular drain-related infection developed in 12(16.2%) patients (95% confidence interval: 4.15-4.75), having external ventricular drain for a mean period of 14.92+/-10.5 days (range 5-40) and 179 total catheter days. Coagulase-negative staphylococcus epidermidis was found in 4(33.3%) and it was sensitive to vancomycin, followed by Klebsiella pneumoniae and Pseudomonas aeruginosa 2(16.7%) each, and they were sensitive to amikacin and colistin, respectively. External ventricular drain-related infection was associated with poor outcomes (p=0.04), a longer intensive care unit stay (p<0.05), a longer hospital stay (p<0.05), and a longer external ventricular drain in-situ (p=0.05). Conclusion: Aseptic external ventricular drain placement and its early removal could avoid external ventricular drain-related infections. Key Words: Extra-ventricular drainage, EVD, EVD-related infection, ERI, Ventriculitis, Hydrocephalus, HCP.